Performance analysis of two component carrier selection algorithms in the downlink LTE-A - Mohd. Ramli, Huda Adibah; Ismail, Ahmad Fadzil; Abdullah, Khaizuran; Sandrasegaran, Kumbesan (IEEE Computer Society, 2013)
This paper studies the performance of two wellknown Component Carrier (CC) selection algorithms in static and dynamic allocation so as to provide satisfactory Quality of Service (QoS) of a Guaranteed Bit Rate (GBR) application. Performance evaluation is conducted using the the downlink Long Term Evolution-Advanced (LTE-A) as the simulation platform. Simulation results demonstrate the efficacy of the Random CC selection algorithm (in dynamic allocation) in optimizing the system capacity without compromising the QoS of the GBR application. However, dynamic allocation comes at the expense of an increase in signalling overhead. Future studies include identification of a new dynamic mechanism for CC selection that can reduce the signalling overhead without compromising the GBR performance.